Bipolar Transurethral Incision of Bladder Neck Stenoses with Mitomycin C Injection. (8th October 2015) - Lyon, Timothy D.; Ayyash, Omar M.; Ferroni, Matthew C.; Rycyna, Kevin J.; Chen, Mang L.
Abstract : Introduction . To determine the efficacy of bipolar transurethral incision with mitomycin C (MMC) injection for the treatment of refractory bladder neck stenosis (BNS). Materials and Methods . Patients who underwent bipolar transurethral incision of BNS (TUIBNS) with MMC injection at our institution from 2013 to 2014 were retrospectively reviewed. A total of 2 mg of 40% mitomycin C solution was injected in four quadrants of the treated BNS. Treatment failure was defined as the need for subsequent intervention. Results . Thirteen patients underwent 17 bipolar TUIBNS with MMC injection. Twelve (92%) patients had failed a mean of 2.2 ± 1.1 prior endoscopic procedures. Median follow-up was 16.5 months (IQR: 14–18.4 months). Initial success was 62%; five (38%) patients had a recurrence with a median time to recurrence of 7.3 months. Four patients underwent a repeat procedure, 2 (50%) of which failed. Overall success was achieved in 77% (10/13) of patients after a mean of 1.3 ± 0.5 procedures. BNS recurrence was not significantly associated with history of pelvic radiation (33% versus 43%, p = 0.9 ). There were no serious adverse events. Conclusions . Bipolar TUIBNS with MMC injection was comparable in efficacy to previously reported techniques and did not result in any serious adverse events.